Mistaking an Emerging Market for a Social Movement? A Comment on Arjaliès’ Social-Movement Perspective on Socially Responsible Investment in France - Déjean, Frédérique; Giamporcaro, Stéphanie; Gond, Jean-Pascal; Leca, Bernard; Penalva-Icher, Elise (2013)
In a recent contribution to this journal, Arjaliès (J Bus Ethics 92:57–78, 2010) suggests that the emergence of socially responsible investment (SRI) in France can be best described as a social movement with a collective identity that aimed to challenge the dominant logic of the financial market. Such an account is at odds with a body of empirical studies that approaches SRI in the French context as a process of market creation led by loosely coordinated actors with contradictory and conflicting interests and values, who have mainly complied with—rather than opposed—the existing dominant financial logic of the asset-management field. In this comment, we build on this prior research to contest Arjaliès’ perspective on both theoretical and empirical grounds, with the aim of highlighting the shortcomings of conflating social movements and other forms of collective actions in understanding the building of new markets in organization theory and SRI studies. We contend that in mistaking for social movement forms of collective actions that underpin the emergence of markets, scholars of organization theory may confuse distinct mechanisms in their explanation of SRI emergence across countries, overlook the complex dynamics and interactions of markets and social movements, and, most importantly, fail to evaluate the real political significance of SRI as an empirical phenomenon. We propose that future research on SRI distinguishes carefully “social-movement research as a theoretical framework” from “social movement as an empirical phenomenon” in order to avoid such drawbacks while benefiting from recent advances in social-movement research.
Keywords: Social-movement research as a theoretical framework; Comparative Studies; Financial markets; Institutionalization; Socially Responsible Investment